The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1175/jas-d-18-0312.1
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Collapse and Recovery in the Stable Boundary Layer Using an Idealized Model of Pressure-Driven Flow with a Surface Energy Budget

Abstract: The evolution of the stable boundary layer is simulated using an idealized single-column model of pressure-driven flow coupled to a surface energy budget. Several commonly used parameterizations of turbulence are examined. The agreement between the simulated wind and temperature profiles and tower observations from the Cabauw tower is generally good given the simplicity of the model. The collapse and recovery of turbulence is explored in the presence of a large-scale pressure gradient, but excluding transient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 82 publications
(120 reference statements)
0
18
0
Order By: Relevance
“…Furthermore, it allows generalizing the conclusions to different locations, by considering different values of soil properties such as its heat capacity and its temperature at larger depths. In contrast with previous studies that used first‐order (Holdsworth and Monahan, ) or TKE models (Baas et al ., ; ), the present use of a complete second‐order version allows investigating the budgets of high‐order moments such as TKE, heat flux and temperature variance both in terms of temporal evolution and vertical structure. The analysis identifies the terms that dominate the respective budgets in the different SBL regimes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it allows generalizing the conclusions to different locations, by considering different values of soil properties such as its heat capacity and its temperature at larger depths. In contrast with previous studies that used first‐order (Holdsworth and Monahan, ) or TKE models (Baas et al ., ; ), the present use of a complete second‐order version allows investigating the budgets of high‐order moments such as TKE, heat flux and temperature variance both in terms of temporal evolution and vertical structure. The analysis identifies the terms that dominate the respective budgets in the different SBL regimes.…”
Section: Introductionmentioning
confidence: 99%
“…() used a similar model to simulate regime transitions observed in Antarctica, finding that such a model reproduces the complex relationship between surface thermal inversion and mean wind speed. Holdsworth and Monahan () looked at the weakly to very stable transition using a first‐order model with turbulent mixing determined by stability functions. They performed idealized equilibrium simulations for different geostrophic winds and found that external factors such as cloudiness, soil thermal conductivity or the Coriolis parameter also affect the SBL regime.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mean wind speed threshold for the transition is not universal, varying from one site to another van Hooijdonk et al 2015). In studies based on simplified numerical models (Van de Wiel et al 2017;Holdsworth and Monahan 2019), it has been suggested that such differences may be associated to different surface characteristics, such as soil properties and the total surface net radiation.…”
Section: Introductionmentioning
confidence: 99%
“…The combined importance of the wind speed and of the surface thermal processes has also been evidenced by numerical studies using idealized single-column models of the atmosphere. Single-column models with a first-order turbulence closure scheme (Baas et al 2017(Baas et al , 2019Holdsworth and Monahan 2019) or a second-order closure scheme (Maroneze et al 2019) are able to representatively simulate transitions from weakly to strongly stable regimes. Yet, direct numerical simulations show that transitions from strongly to weakly stable regimes can occur following a localized, random perturbation of the flow (Donda et al 2015).…”
Section: Introductionmentioning
confidence: 99%